KESALAHAN SISWA MENYELESAIKAN SOAL CERITA KPK DAN FPB BERDASARKAN PROSEDUR NEWMAN - Ruslan, Ruslan; Yani, Ahmad; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine type of student errors in solving word problem of LCM and HCF based on Newman's procedures. Subjects in this study were students of class VII MTS Darul Amin Pontianak, totaling 17 people. The method used in this research is descriptive method with a case study approach. Data collection techniques used in this study were written tests. The results showed students made mistakes answering questions on each Newman procedure. In first question, 3 students make comprehension errors (2 students understood the LCM problem as a HCF problem, 1 student can't continue the answer), 9 students make transformation errors (8 students solve LCM problems only takes the same prime factor from both numbers that have the highest rank., 1 students solve LCM with multiplying same smallest multiple from both numbers), 1 students make encoding errors (didn’t write the final answer according to the question request). In the second question, 2 students make comprehension errors (solve HCF problem by taking all the prime factors with the highest rank.), 1 students make process skills errors (can’t do multiplication operations correctly), 4 students make encoding errors (student didn’t write the final answer according to the question request) Keywords: HCF, LCM, Newman’s Procedure, Word Problem